Evaluasi Dampak Keberadaan Juru Parkir Liar terhadap Perilaku Konsumen Generasi Z di Depan Usaha Mikro di Kecamatan Rappocini - Muhammad Fadel Dinero; M. Ikhwan Maulana Haeruddin; M. Ilham Wardhana Haeruddin; Sitti Hasbiah; Ilma Wulansari Hasdiansa (Universitas Katolik Widya Karya Malang, 2025)
This research objective is to further evaluate how the presence of illegal parking attendants affects consumer behavior, particularly Generation Z, in deciding to visit and transact at MSMEs in Makassar City. This study aims to analyze Generation Z's perception of the presence of illegal parking attendants around micro-enterprises in Rappocini District, Makassar City, and its impact on consumer behavior. This research uses a qualitative approach with in-depth interviews of 15 Generation Z informants who are consumers of micro-enterprises in the area. The research findings indicate that the majority of informants feel uncomfortable with the presence of illegal parking attendants due to what they perceive as forced fees, a lack of vehicle security guaranties, and additional burdensome costs. This condition affects the shopping experience and makes some consumers reluctant to return to certain business locations. However, some informants stated that the presence of illegal parking attendants did not significantly influence their decisions due to factors such as location proximity, habit, and relatively affordable rates.